Smart Make an Autonomous "Follow Me" Cooler (The Peerian Journal, 2022)
In this project, we use an Arduino Uno to build an autonomous "follow me" cooler. The robot cooler connects to a smartphone via Bluetooth and uses GPS to navigate. All the electronics will be contained in the base so that other objects can be carried as well.